Extending knowledge of the public awareness of aphasia in the Balkans: Serbia and Montenegro. Issue 23 (6th November 2017) - Vuković, Mile; Matić, Dušanka; Kovač, Ana; Vuković, Irena; Code, Chris
Abstract: Purpose: Public awareness of aphasia has been surveyed in a number of countries revealing that it is universally low. We report results of surveys in the Balkan countries Serbia and Montenegro and compare results with data from Croatia and Slovenia. Methods: Convenience surveys of the general public were conducted in public places like shopping centers/malls and parks in Serbia ( N  = 400) and Montenegro ( N  = 500) using an adapted version of the public awareness of aphasia survey questionnaire. Respondents were asked whether they have heard of aphasia and tested with questions about aphasia. Information on gender, age, occupation and education was recorded. Outcomes: Twelve percent (Serbia) and 11% (Montenegro) had heard of aphasia, but just 4% (Serbia) and 3.2% (Montenegro) had a basic knowledge of aphasia. Age, gender and occupation interacted variably with awareness. Between 16% (Slovenia) and 60% (Croatia) said they had heard of aphasia (10.5% overall mean for the four countries) and basic knowledge of aphasia across the four countries ranged between 3.2 and 7%. Conclusions: Levels of awareness of aphasia in the Balkans are low and variably associated with age, gender, socio-economic and educational levels. Respondents with some knowledge of aphasia gained it through personal or professional interaction with aphasia or the media. The data provide a basis for awareness raising in Balkan countries to reduce stigmatization, improve community access and understanding. Implications for rehabilitation: Awareness of aphasia is low universally, even among healthcare workers. Low public awareness of a condition, like aphasia, results in under-funded research and service provision. In order to raise public awareness of aphasia we need to know how many members of the general public know about it. Improvements in public awareness could positively affect funding, the quality of services, and the public understanding and acceptance of individuals with aphasia in the community. Improving awareness of aphasia in those who come into contact with aphasic people, like healthcare workers, could significantly improve the healthcare experience of people with aphasia and their families.